Methods of Qur'anic memorisation (hifz): implications for learning performance - Dzulkifli, Mariam Adawiah; Solihu, Abdul Kabir Hussain (IIUM Press, International Islamic University Malaysia, 2018)
Memorisation of the Qur’ān occupies a central position in Muslim conception of religious education. The awareness of preserving the Qur’ān through memorisation (ḥifẓ) is becoming prevalent and is still continued in these modern days in many educational institutions in many parts of the Muslim countries. This article examines different methods of Qur’ānic memorization being practiced in Malaysia. Similarities and uniqueness of those methods will be presented. The evaluation of those Qur’ānic memorisation techniques brings to the foreground the educative value of memorisation as a learning tool and the implications memorisation methods have in enhancing an individual’s learning performance. ********************************************************** Penghafalan Al-Qur’an menduduki kedudukan sentral dalam konsepsi Muslim mengenai pendidikan berkaitan agama. Kesedaran untuk memelihara Al-Qur’ān melalui penghafalan (ḥifẓ) menjadi semakin ketara dan masih diteruskan pada zaman moden ini di banyak institusi-institusi pendidikan di banyak bahagian negara-negara Islam. Artikel ini meneliti pelbagai kaedah penghafalan Qur’ān yang diamalkan di Malaysia. Persamaan dan keunikan kaedah-kaedah tersebut akan dibentangkan. Penilaian terhadap kaedah-kaedah penghafalan Qur’ān tersebut membawa kepada rumusan mengenai nilai pendidikan melalui kaedah penghafalan sebagai satu alat pembelajaran dan implikasinya dalam meningkatkan prestasi pembelajaran individu.